Screening of Saccharum spp. genotypes for sugarcane yellow leaf virus resistance by combining symptom phenotyping and highly precise virus titration - Burbano, Roberto C.V. [UNESP]; Gonçalves, Marcos C.; Nobile, Paula M.; dos Anjos, Ivan A.; da Silva, Marcel F.; Perecin, Dilermando [UNESP]; Anjos, Luciana O.S.; Fernandes, Vivian B.V.R.; Pinto, Luciana R. (Elsevier, 2021)
Yellow leaf disease (YLD), caused by sugarcane yellow leaf virus (SCYLV), has been reported to infect sugarcane worldwide causing significant yield losses and is considered a major disease of this crop. A panel composed of 98 genotypes encompassing basic germplasm, commercial cultivars, and elite clones was assayed in the nursery and a replicated field for resistance to SCYLV, combining symptom expression and virus quantification. Virus symptom intensity was evaluated using a diagrammatic scale while virus titer was estimated by DAS-ELISA (Double Antibody Sandwich-ELISA) and RT-qPCR (Reverse Transcription Quantitative PCR) in the nursery and field trials, respectively. Resistance was evaluated alongside symptom development kinetics. Based on the symptom intensity, 52 (53.06%) genotypes were classified as resistant in the nursery and 42 (42.86%) in the field. Twenty-nine (29.59%) genotypes showed no symptoms in the nursery and field trial. Moderately resistant genotypes showed a low correlation between virus titer and symptom intensity. The kinetics of symptom development increased over time in moderately susceptible and susceptible genotypes. The SCYLV incidence assessed by RT-qPCR was 92.55%, which was detected in 83% of the asymptomatic genotypes. The broad-sense heritability based on symptom expression and relative quantification was 52.62% and 68%, respectively. The virus quantification assays allowed for the identification of potential genotypes immune to SCYLV.
Keywords: DAS-ELISA; Phenotyping; Polerovirus; RT-qPCR; Sugarcane; Yellow leaf disease